Physiology practicals - Nováková, Marie (Masarykova univerzita, 2007)
The general objective of Physiology Practicals among others is to offer and introduction to scientific way of medical thinking. the student should aslo acquire some basal skills in handling the instruments, currently employed in medical practice. But above all, the student should be motivated to study the functions from molecules to the whole organism and to comprehend their interrelationships, the very essence of modern medicine.
Keywords: Physiology; fyziologie